PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA KARYAWAN PT. BANK TABUNGAN NEGARA (PERSERO) TBK. KANTOR CABANG SIDOARJO - Fatwa, Kintan Septarina; Adiwati, Mei Retno (Yayasan Education and Social Center, 2023)
Employee discipline serves as the primary foundation to achieve the company's goals. However, several factors can influence a company's success or failure, namely leadership and work motivation. This research aims to comprehend the influence of leadership and work basis on employee work discipline at PT. Bank Tabungan Negara (Persero) Tbk. Sidoarjo Branch. A saturation sampling technique is employed for sample selection in this research, which involves the entire population existing in PT. Bank Tabungan Negara (Persero) Tbk. Sidoarjo Branch, totaling 88 respondents. This research uses a questionnaire directly administered to the respondents. The analysis method utilized Partial Least Squares (PLS). The research findings demonstrate that leadership and work motivation impact the work discipline of employees at PT. Bank Tabungan Negara (Persero) Tbk. Sidoarjo Branch